HTLV-1 and other viral sexually transmitted infections in antenatal and gynaecological patients in Ghana - Apea-Kubi, K.A.; Yamaguchi, S.; Sakyi, B.; Ofori-Adjei, D. (West African Journal of Medicine, 2006)
Background: The study was undertaken to determine the prevalence of infection with Human T cell lymphotrophic (leukemia) virus-1 (HTLV-1), Hepatitis B virus, Hepatitis C virus and Human Immunodeficiency Virus (HIV) in patients attending the antenatal and gynaecological outpatient clinics at Korle-Bu Teaching Hospital (KBTH). Design: Prospective observational survey. Serum from each of the 517 participants was analysed for infection with Hepatitis B surface antigen with a latex agglutination test kit (Biotech Laboratories Ltd., Suffolk, United Kingdom), and tested for antibodies to Human Immunodeficiency Virus (HIV), Hepatitis C virus, and Human T cell lymphotrophic (leukemia) virus-1 (HTLV-1) with SERODIA passive-particle agglutination assay kits (FUJIREBIO Inc., Tokyo, Japan). The results were compared with reports from other institutions. Settings: The Obstetrics and Gynaecology outpatient clinics of the Korle-bu Teaching Hospital, Accra, Ghana. The virology Unit of the Noguchi Memorial Institute for Medical Research (NMIMR), Accra, Ghana. Results: The prevalence of infection with Hepatitis B surface antigen (HBsAg) was 16.8%, Hepatitis C antibody 5.2% and HTLV-1 2.7%. Twelve (6%) out of 199 participants who gave informed consent tested positive for HIV antibody. Conclusions: The study has demonstrated a high transmissible risk of HBV, HIV, HTLV-1, and HCV in Ghana and the necessity for antenatal screening for HBsAg to identify babies at risk of neonatal hepatitis B infection for appropriate intervention.
Keywords: Antenatal; Ghana; HTLV-1; Korle-Bu Teaching Hospital; Viral-STIs